Qualidade e segurança alimentar do milho em diferentes acondicionamentos de armazenagem - Domenico, Adriana Sbardelotto Di (2014)
Brazil is one of the largest producers of grains, and maize is the second most produced grain in the country. As this cereal is directly related to human and animal food basis, many matters appear on the maintenance of their post-harvest quality, especially during storage, due to the increased attention to food safety. Despite this importance, maize is often stored on farms in inappropriate conditions, exposed to quantitative and qualitative losses, the development of toxigenic fungi and aflatoxin contamination, a substance capable of causing severe damage to human and animal health, as well as many agribusiness losses. The objective of this research was evaluating storage alternatives viable to farms through two storage experiments (2012 winter crop 2012/2013 summer harvests), for assessment of the quality of stored maize in different packings for 12 months. The experimental design was a 4 x 5 factorial, whose factors were four types of packaging storage (conventional sacks, bags hermetically sealed, metallic silo and cobs) and five time periods (0, 3, 6, 9 and 12 months). Two maize hybrids (2B688RR, 30K73Hx) cultivated in the region of the town of Dois Vizinhos were used, in the southwest of Paraná. The storage was conducted in ambient conditions and the following parameters were evaluated: water content, ash, protein, fat, grains without defects, volumetric weight, one-thousand grains weight, counting of Aspergillus sp, Fusarium sp, Penicillium sp, total of molds and yeasts and occurrence of aflatoxins (B1, B2, G1 and G2). The results obtained in each experiment, when attended the presuppositions of the mathematical model, were evaluated by use of analysis of variance and differences between means (p<0.05) by Tukey test at 5% significance level, and when not attended them, by Kruskal-Wallis also at 5% significance level. Furthermore, the Principal Component Analysis (PCA) was done to determine which of the variables evaluated was responsible for the largest variations in the quality of stored maize. It was found in both storages that maize kernels placed in sealed bags presented the lowest water content. Also that regardless of packaging and hybrid maize, there were an increase in ash content of grains and the decrease of the percentage of grains without defects and volumetric weight. It was detected the incidence of Aspergillus sp. Fusarium sp. and Penicillium sp., respectively 20.37, 86.11 and 94.44% of the samples of maize season winter storage, and in 83.3, 91.6 and 90.07% of the samples from the summer season storage. Aspergillus sp. was only detected after 3 months of storage in the first experiment, while in the second since harvesting. The occurrence of Fusarium sp. tended to decrease during storage, and Penicillium sp. was higher in corn conditioning in cobs. There was no influence of types of packaging and storage time on the occurrence of Aspergillus sp. and aflatoxins in maize season winter storage. However, the conditioning in maize cobs of season storage summer had the lowest count of Aspergillus sp. and did not present aflatoxin. Aflatoxins (B1+B2+G1+G2) detected ranged from 2.77 to 14.45 μg kg-1 and from 3.03 to 197.51 μg kg-1 respectively in the maize storage winter and summer. Besides this, none of the samples of the first storage showed contamination higher than 20 μg kg-1, while in the second 41 samples presented higher values. The results are due to the different climatic conditions of the periods of cultivation of hybrid maize (summer and winter seasons) and storage experiments, the disparity in the incidence of Aspergillus sp. and aflatoxin contamination. The conclusion is that by ACP all variables assessed in this study are important for the quality of stored maize.